1997
DOI: 10.1089/apc.1997.11.331
|View full text |Cite
|
Sign up to set email alerts
|

AIDS and HIV Infection in Sudanese Children: A Clinical and Epidemiological Study

Abstract: HIV surveillance and screening programs were established at Khartoum Teaching Hospital (KTH) following the first identified HIV case diagnosed in a hemophiliac boy in November 1987. As of December 1995, 15 cases of symptomatic HIV infection have been observed in Sudanese children (< or = 16 years) at KTH. An HIV seroprevalence rate of 35.7% was documented in a group of 28 patients (adults and children) with various congenital coagulation defects. The postulated mode of transmission was through contaminated fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…However, only TB, parotiditis and AOM could be considered as indicators of HIV-infection since their prevalence was significantly correlated with decreased CD4+ T cell resulting from HIV infection. Despite the small sample size used in this study, our findings are in agreement with reports from Nigeria 17, South Africa (18) and Sudan (19) which observed a wide range of clinical manifestations in HIV-infected children. In this study, however, only TB, parotiditis and AOM were identified as indicator opportunistic infections in children infected with HIV-1.…”
Section: Discussionsupporting
confidence: 92%
“…However, only TB, parotiditis and AOM could be considered as indicators of HIV-infection since their prevalence was significantly correlated with decreased CD4+ T cell resulting from HIV infection. Despite the small sample size used in this study, our findings are in agreement with reports from Nigeria 17, South Africa (18) and Sudan (19) which observed a wide range of clinical manifestations in HIV-infected children. In this study, however, only TB, parotiditis and AOM were identified as indicator opportunistic infections in children infected with HIV-1.…”
Section: Discussionsupporting
confidence: 92%
“…A total of 12 eligible articles were found determining prevalence of HIV antibodies in Sudan [ 10 21 ]. The total sample size of participants was 15,479.…”
Section: Resultsmentioning
confidence: 99%
“…This corroborates the findings in studies from other parts of the country, [3][4][5] with higher rates of tuberculosis co-infection documented in studies from India and Sudan. [9,25,26] However, reports from Africa have consistently shown that respiratory conditions are a major cause of morbidity and mortality among HIV-infected children. [3][4][5]9,27] Children in this study, especially those under 5 years of age, had advanced disease as indicated by their clinical features, severe malnutrition, and profound immunosuppression on presentation.…”
Section: Discussionmentioning
confidence: 99%